Implementation of Sharia Marketing to increase Millennial Interest in Financing: Evidence on BSI Dharmawangsa Branch Office - Yudha, Ana Toni Roby Candra; Zulfiah, Hilya; Atho'illah, Akh. Yunan (Institut Agama Islam Negeri Ponorogo, 2024)
Bank Syariah Indonesia (BSI provides BSI Griya Simuda financing that has been tailored to the needs and abilities of the millennial generation. Marketing carried out in Islamic financing must be in accordance with the provisions of Islamic sharia. So this research aims to find out the implementation and evaluation of online and offline sharia marketing in increasing millennial interest in financing of BSI Griya Simuda.. Research Methods: This research approach uses a qualitative approach, by analysing data obtained from interviews, observation and documentation. Results: The results of this research show that in marketing BSI Griya Simuda financing in managerial and operational had carried out online and offline have applied the principles of sharia marketing and the characteristics of sharia marketing, namely theistic (rabbaniyyah), ethical (akhlaqiyyah), realistic (al-waqiyyah) and humanitis (al-insaniyah). Conclusion:Then the results of the evaluation found that the millennial generation's interest in BSI Griya Simuda financing is good, but in marketing there are obstacles and challenges, namely there are still efforts to compare conventional banks with Islamic banks in terms of prices and products.